The Management of Audience Discomfort: FIX&FOXY’s Practice of Political Confrontation - Schultz, Laura Luise (Peripeti, 2023)
Laura Luise Schultz describes the approach to the audience in various of performances and highlights, that a central feature of FIX&FOXY's political remediation is their sophisticated engagement with the audience and managing of the audience's discomfort.